Serotype Diversity and Antimicrobial Resistance Profile of Salmonella enterica Isolates From Freshwater Turtles Sold for Human Consumption in Wet Markets in Hong Kong - Colon, Violaine Albane; Lugsomya, Kittitat; Lam, Hoi Kiu; Wahl, Lloyd Christian; Parkes, Rebecca Sarah Victoria; Cormack, Catherine Anne; Horlbog, Jule Anna; Stevens, Marc; Stephan, Roger; Magouras, Ioannis (Frontiers in Veterinary Science, 2022)
Chelonians are recognized as a source of human salmonellosis through direct contact or consumption of their meat. Freshwater turtles sold for food are widely available in wet markets in Asia. In this pilot study, 50 turtles belonging to three species were randomly sampled from wet markets throughout Hong Kong. The turtles were humanely euthanised and their feces or the colon were sampled for Salmonella culture. The Salmonella isolates obtained were serotyped and examined for phenotypic antimicrobial resistance and the presence of antimicrobial resistance genes. The study reports a high prevalence (42%, 95% CI: 29.4–55.8) and considerable serotype diversity of Salmonella among turtles sold in wet markets. The most common among the 11 serotypes isolated were S. Oranienburg and S. Thompson, which have been reported in turtles previously. The serotype S. Manhattan is reported in chelonians for the first time. Resistance to streptomycin and chloramphenicol was common, despite the latter being banned from aquaculture in mainland China since 2002. Resistance against fluoroquinolones and third-generation cephalosporins which represent first-line treatment options for salmonellosis was also observed. The multidrug-resistance gene cfr is identified for the first time in Salmonella. This is a worrying finding as it indicates an expansion of the cfr reservoir and potential horizontal spread to other bacteria. The results of this study emphasize the need for close surveillance of Salmonella from turtles sold as food and better regulation of turtle farming to safeguard public health and improve animal welfare.